Tingkat Kesiapan Penggunaan Teknologi Pengemudi Layanan Transportasi Online Go-Jek Di Bali - Manurung, David Yohanes; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT The height of Indonesian internet users using smartphones is the reason for Go-jek’s online transportation service to emerge. Go-jek is a taxi booking through a smartphone application that can be downloaded. Go-jek is expected to provide solutions and to address public concerns about the public transportation service. The goal of this research is to learn driver’s technology readiness using Go-jek application. Using the concept of technology readiness index and a quantitative approach of research, the result of this research that Go-jek drivers in Bali are explorers type of the five types of technology customers. Research show the driver has a positive view of Go-jek application. Drivers had the motivation and confidence to use technology and often learned much about new technologies. So, Go-jek drivers in Bali had no problem using the application that communication on the part of Go-jek drivers with the customers is going well. Keywords : Driver, Go-jek, Online Transportation, Technology Readiness